Пам’ять про Голокост у символічному просторі Дніпра (Дніпропетровська) - Медведовська, А. (Місто: історія, культура, суспільство, 2020)
У статті на основі аналізу особливостей роману Юрія Винничука «Танґо смерті» проаналізовано авторські наративні стратегії переосмислення на прикладі Львова сюжетів міської історії у 1930–1940-х роках, реконструкції колективної і персональних пам’ятей містян. Проаналізований письменницький текст є суттєвим прикладом «вписування» Львова у пам’яттєвий дискурс сучасної української літератури, а тому має два часові зрізи – довоєнний/воєнний (міжвоєнний період, роки Другої світової війни) і сучасний. Досліджувані події вивчаються як історія містян (зокрема взаємин дітей бійців Армії УНР, розстріляних 1921-го під Базаром), які є носіями різних, часто конфліктних національних ідентичностей, виклику щодо можливостей реконструкції пам’яті про «спільний» Львів в умовах військово-політичного конфлікту і радикального загострення міжнаціональних взаємин, а також як відновлення пам’яті про Янівський концентраційний табір. Стверджується, що уявну та справжню поліфонію взаємин у передвоєнному Львові (як і в інших містах Галичини), а також дитинство-юність героїв «історичної» частини роману Ю. Винничука руйнує вересень 1939 року. Події Другої світової війни, описані на прикладі Львова, є важливим компонентом міської пам’яті, а пережиті страждання героїв роману можна назвати одним із потужних детермінантних елементів національної ідентичності. У своєму романі Ю. Винничук вдається до отілеснення музики, інсценізуючи текст роману як «танґо», створюючи тим самим партитуру поліфонічності Львова з міста-перехрестя у місто-жертву з його мешканцями. На прикладі роману Ю. Винничука показано, що «львівська» пам’ять є маркером темпорального горизонту, зокрема комунікативна пам’ять передає історичний досвід міста у межах індивідуальних біографій протагоністів роману за допомогою живих спогадів, безпосереднього досвіду й усної оповіді. Запропоновано розглядати письменника як носія мнемонічного інформаційного ресурсу, того, хто накопичує пам’ять про трагічні сторінки міської історії і ретранслює до своїх сучасників. Аналіз роману Ю. Винничука «Танґо смерті» показує, що, по-перше, Львів є прикладом не так символічного, як цілком реального місця пам’яті, і, по-друге, підтвердженням сучасної тези А. Ассман про місце пам’яті, що «освячене присутністю мертвих». This article aims to demonstrate the key transformations that took place at the Holocaust sites in the Dnipro (former Dnepropetrovsk) from the end of the Nazi occupation to the present day. It explores the extent to which these locations have become places of the Holocaust commemoration and describes the mechanisms and features of inclusion of such commemoration into the city’s urban space. The author analyzes the main initiators and supporters of the Holocaust commemoration in order to evaluate how effectively the history of the extermination of Jews is represented in urban space of Dnipro and how much it corresponds to its contemporary image. The article, based on existing historiography, describes events in the three main locations of the Holocaust in Dnepropetrovsk (Dnipro), where the most large-scale acts of extermination of the Jewish population took place – near the Botanical Garden (Krasnopovstanska Balka), the Jewish Cemetery (Park of Pisarzhevsky), the village of Verkhnie (the intersection of Yangel and Energeticha streets. Sufficient body of research provides a fairly reliable evidence of what took place in the aforementioned locales during the Nazi occupation. An important feature that subsequently influenced the commemoration of these places in both the Soviet and the post-Soviet periods was that in the first location, i.e. in the Krasnopovstanska Balka (ravine), those executed were exclusively Jewish, while in the other two locations, different categories of Nazi victims were executed, including a significant number of Jews. In the 1960-1980s, a period of honoring the history of the Great Patriotic War, monuments, erected to commemorate the victims, only bore inscriptions, typical for the Soviet officialdom. These inscriptions did not mention the ethnic origin of Jewish victims, dissolving them in euphemistic formulations, such as “civilians”, “Soviet citizens”, etc. After the collapse of the USSR, old taboos were lifted and previously forbidden historical facts and narratives, including the identity of national groups claiming their place in historical consciousness began to take shape. This article analyzes various combinations of memorial discourses – Soviet and Jewish / Soviet and post-Soviet / Jewish, Soviet and Ukrainian – and how they relate (interact / conflict / do not communicate) in the mentioned locations. Based on her analysis, the author concludes that the city’s Jewish community was the main initiator and supporter of the preservation of the Holocaust memory, which has led to high degree of fragmentation of the commemoration of the Holocaust in Dnipro. Nevertheless, thanks to the collaboration and occasional joint activities of Jewish organizations, as well as Dnipro’s public and governmental institutions, the memory of Holocaust has become gradually incorporated into the urban space, where it occupies a more prominent place.